Complex Magnetic Nanostructures : Synthesis, Assembly and Applications - Sharma, Surender Kumar (Springer International Publishing : Imprint: Springer, 2017)
This book offers a detailed discussion of the complex magnetic behavior of magnetic nanosystems, with its myriad of geometries (e.g. core-shell, heterodimer and dumbbell) and its different applications. It provides a broad overview of the numerous current studies concerned with magnetic nanoparticles, presenting key examples and an in-depth examination of the cutting-edge developments in this field. This contributed volume shares the latest developments in nanomagnetism with a wide audience: from upper undergraduate and graduate students to advanced specialists in both academia and industry. The first three chapters serve as a primer to the more advanced content found later in the book, making it an ideal introductory text for researchers starting in this field. It provides a forum for the critical evaluation of many aspects of complex nanomagnetism that are at the forefront of nanoscience today. It also presents highlights from the extensive literature on the topic, including the latest research in this field.
Keywords: Materials science.; Nanochemistry.; Magnetism.; Magnetic materials.; Nanoscale science.; Nanoscience.; Nanostructures.; Nanotechnology.; elektronické knihy; electronic books